Does candidate for plate fixation selection improve the functional outcome after midshaft clavicle fracture? A systematic review of 1348 patients. (February 2019) - Vautrin, M; Kaminski, G; Barimani, B; Elmers, J; Philippe, V; Cherix, S; Thein, E; Borens, O; Vauclair, F
Introduction: The hypothesis of this study was that patient selection for midshaft clavicle fracture (open reduction internal fixation with plate versus conservative) would give better functional outcome than random treatment allocation. Methods: We performed a systematic literature search for primary studies providing functional score and non-union rate after conservative or surgical management of midshaft clavicle fractures. Six randomized controlled trial and 19 non-randomized controlled trial studies encompassing a total of 1348 patients were included. Results: Patients treated with surgical management were found to have statistically superior Constant scores in non-randomized controlled trials than in randomized controlled trials (94.76 ± 6.4 versus 92.49 ± 6.2; p < 0.0001). For conservative treatment, randomized controlled trials were found to have significantly better functional outcome. The prevalence of non-union (6.1%) did not show significant statistical difference between non-randomized controlled trial and randomized controlled trial studies. The functional outcome after surgical management was significantly higher than after conservative management in both randomized controlled trial and non-randomized controlled trial groups. The non-union rate after surgery (1.1% for both non-randomized controlled trial and randomized controlled trial) was significantly lower than following conservative treatment (9.9% non-randomized controlled trial versus 15.1% randomized controlled trial). Discussion: This review shows that patient selection for surgery may influence functional outcome after midshaft clavicle fracture. Our results also confirm that plate fixation provides better functional outcome and lower non-union rate.